S1P defects cause a new entity of cataract, alopecia, oral mucosal disorder, and psoriasis‐like syndrome. Issue 5 (1st April 2022) - Chen, Fuying; Ni, Cheng; Wang, Xiaoxiao; Cheng, Ruhong; Pan, Chaolan; Wang, Yumeng; Liang, Jianying; Zhang, Jia; Cheng, Jinke; Chin, Y Eugene; Zhou, Yi; Wang, Zhen; et al.
Abstract: In this report, we discovered a new entity named cataract, alopecia, oral mucosal disorder, and psoriasis‐like (CAOP) syndrome in two unrelated and ethnically diverse patients. Furthermore, patient 1 failed to respond to regular treatment. We found that CAOP syndrome was caused by an autosomal recessive defect in the mitochondrial membrane‐bound transcription factor peptidase/site‐1 protease ( MBTPS1, S1P). Mitochondrial abnormalities were observed in patient 1 with CAOP syndrome. Furthermore, we found that S1P is a novel mitochondrial protein that forms a trimeric complex with ETFA/ETFB. S1P enhances ETFA/ETFB flavination and maintains its stability. Patient S1P variants destabilize ETFA/ETFB, impair mitochondrial respiration, decrease fatty acid β‐oxidation activity, and shift mitochondrial oxidative phosphorylation (OXPHOS) to glycolysis. Mitochondrial dysfunction and inflammatory lesions in patient 1 were significantly ameliorated by riboflavin supplementation, which restored the stability of ETFA/ETFB. Our study discovered that mutations in MBTPS1 resulted in a new entity of CAOP syndrome and elucidated the mechanism of the mutations in the new disease. Synopsis: Autosomal recessive variants in MBTPS1 gene cause a new entity of cataract, alopecia, oral mucosal disorder and psoriasis‐like (CAOP) syndrome. Further in vitro and in vivo analyses confirmed the pathogenicity of MBTPS1 variants. Our study also demonstrates that the CAOP syndrome patient was responsive to riboflavin treatment. S1P interacts with and flavinates the electron transferring flavoprotein (ETF). Inefficient import of mutant S1P into mitochondria impairs mitochondrial respiration and shifts mitochondrial oxidative phosphorylation (OXPHOS) to glycolysis. Riboflavin supplementation increases ETF stability and restores mitochondrial dysfunction and inflammatory lesions in patient. Abstract : Autosomal recessive variants in MBTPS1 gene cause a new entity of cataract, alopecia, oral mucosal disorder and psoriasis‐like (CAOP) syndrome. Further in vitro and in vivo analyses confirmed the pathogenicity of MBTPS1 variants. Our study also demonstrates that the CAOP syndrome patient was responsive to riboflavin treatment.